Indonesia-Malaysia Cooperation in Human Rights Criminal Law Enforcement - Mohammad Ali; Muhammad Al Kindy; Elmi Sasmitanigtyas; Anastasia Kolo (CLEAR: Criminal Law Review, 2024)
This study aims at analyzing the form of bilateral cooperation between Indonesia and Malaysia in enforcing Human Rights (HAM), with a focus on the role of Constitutional Law in framing state obligations in such cooperation. Although ASEAN has a human rights mechanism, the effectiveness of ASEAN Intergovernmental Commission on Human Rights (AICHR), is limited. Thus, it raises the significant of bilateral cooperation between ASEAN member countries, especially Indonesia and Malaysia. A qualitative approach with a descriptive analytical method was geared to explore a deeper understanding of the implementation of this cooperation. The results of interviews with officials from the Indonesian and Malaysian Ministries of Foreign Affairs revealed that although there are several bilateral agreements involving the protection of migrant workers and combating human trafficking, implementation in the field is hampered by unclear law enforcement and differences in interpretation of state obligations. Despite the agreement between the two countries, the biggest obstacle lies in the weak governance mechanism and the inconsistency of the legal systems between Indonesia and Malaysia. In this context, Indonesian Constitutional Law plays an important role in ensuring that any international cooperation, including Malaysia, must be approved by the House of Representatives (DPR) to avoid violating the constitutional principles and human rights. The recommendation from this study is the importance of strengthening the monitoring mechanism and capacity of related institutions, to ensure better protection for Indonesian migrant workers in Malaysia and optimize bilateral cooperation in enforcing human rights